DAMPAK PARIWISATA TERHADAP STRUKTUR EKONOMI NTB: PELUANG DAN TANTANGAN - Agustiani, Eka; M. Rifki, Lalu; Dwi Pradana, I Made; Juliana, Nursalwah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study examines the impact of tourism sector growth on the economic structure of West Nusa Tenggara (NTB) Province. Over the past decade, NTB has experienced a significant surge in tourism driven by national strategic projects such as the Mandalika Special Economic Zone (SEZ) and the MotoGP. This study aims to analyze the extent to which tourism has shifted the economic structure from primary to tertiary sector dominance, as well as to identify emerging opportunities and challenges. The methods used include analysis of secondary data from the Statistics Indonesia (BPS) and the NTB Tourism Office (Dispar), using the Location Quotient (LQ), Shift-share, and multiplier effects approaches. The results indicate that service sectors such as accommodation, food and beverage, and transportation have increased their contribution to NTB's GRDP. Tourism also provides significant opportunities for MSMEs and job creation, but this distribution is not yet fully equitable across regions. Inequality in infrastructure between regions, human resource quality, and environmental degradation are key challenges. Regional governments need to develop inclusive and sustainable governance so that the benefits of tourism are not limited to certain regions. This research contributes to the literature on regional economic transformation and the strengthening of data-driven policies in the tourism sector.